2006
DOI: 10.1177/1090198106288498
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of a Faith-Based Breast and Cervical Cancer Screening Intervention for African American Women

Abstract: This article presents a formative evaluation of a CDC Racial and Ethnic Approaches to Community Health (REACH) 2010 faith-based breast and cervical cancer early detection and prevention intervention for African American women living in urban communities. Focus groups were conducted with a sample of women (N=94) recruited from each church participating in the intervention. One focus group was conducted in each of the nine participating churches following completion of the 6-month REACH 2010 intervention. Transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…37 More recently, churches have served as important centers for health promotion interventions. 38,39 Although faith-based interventions for HIV prevention and education have been shown to be feasible and effective in African American churches, 33,40 existing HIV/AIDS stigma has been reported as a barrier to HIV program implementation. 41 Coleman et al argue that pastors and church leaders can play a crucial role in mediating the church environment in a way that promotes empathy and acceptance of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…37 More recently, churches have served as important centers for health promotion interventions. 38,39 Although faith-based interventions for HIV prevention and education have been shown to be feasible and effective in African American churches, 33,40 existing HIV/AIDS stigma has been reported as a barrier to HIV program implementation. 41 Coleman et al argue that pastors and church leaders can play a crucial role in mediating the church environment in a way that promotes empathy and acceptance of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…was this attitude or belief held by other members in the same focus group?) (Mathews, Berrios, Darnell, & Calhoun, 2006). Both authors also checked transcripts alongside recorded tapes several times for accuracy before coding to identify the emerging themes and for greater reliability and validity of data (Lincoln & Guba, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined the association between religiosity and the reduced risk of illnesses such as cancer and hypertension, statistically associating religious values and beliefs with protective factors against these diseases and increasing the median survival time significantly (e.g., Aldridge, 2000;Calderón, 1997;Kaplan, Calman, Golub, Raddock, & Billing, 2006;Mathews, Berrios, Darnell, & Calhoun, 2006;Woods & Ironson, 1999). Other studies have shown a reduced mortality among people who regularly attend church services (Ironson, Stuetzle, & Fletcher, 2006).…”
Section: Role Of Religiosity In Healthmentioning
confidence: 99%